2019
DOI: 10.3390/geosciences9060250
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Cultural Heritage and Resources Threatened by Climate Change

Abstract: With a wide spectrum of data, case studies, monitoring, and experimental and numerical simulation techniques, the multidisciplinary approach of material, environmental, and computer science applied to the conservation of cultural heritage offers several opportunities for the heritage science and conservation community to map and monitor the state of the art of the knowledge referring to natural and human-induced climate change impacts on cultural heritage—mainly constituted by the built environment—in Europe a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 12 publications
(29 reference statements)
0
28
0
Order By: Relevance
“…Given the effective role of stakeholders in defining cultural heritage value [53] from the territorial point of view, this study also emphasizes the critical role of education and knowledge exchange across a wide range of stakeholders [42], including heritage management, trans disciplinary research, and climate science. This insight facilitates the engagement of the local community in protection of cultural heritage resources [54], and provide an influential base for redefining the cultural heritage concept and climate-resilience policies in the era of climate change. This policies should include new approaches that support multi-scale and multi-sector action rooted in the different expectations of a wide range of partners, expand the scope of community participation and engagement.…”
Section: Discussionmentioning
confidence: 96%
“…Given the effective role of stakeholders in defining cultural heritage value [53] from the territorial point of view, this study also emphasizes the critical role of education and knowledge exchange across a wide range of stakeholders [42], including heritage management, trans disciplinary research, and climate science. This insight facilitates the engagement of the local community in protection of cultural heritage resources [54], and provide an influential base for redefining the cultural heritage concept and climate-resilience policies in the era of climate change. This policies should include new approaches that support multi-scale and multi-sector action rooted in the different expectations of a wide range of partners, expand the scope of community participation and engagement.…”
Section: Discussionmentioning
confidence: 96%
“…It has been demonstrated that pollution and climate change not only damage human health, but also endanger the conservation of materials, because artistic surfaces also interact with the surrounding environment. Recent studies established a correlation between environmental decay and increasing degradation [17][18][19]. The evaluation of damage due to an aggressive environment and the identification of possible solutions represent a very challenging task, particularly if the proposed solutions are avant-garde, green, and safe.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change inflicts direct damage on the materials and structure of historical monuments [13] and threatens the status of Outstanding Universal Value at many World Heritage Sites [14]. For instance, the United Kingdom Climate Impacts Programme (UKCIP) has suggested that the sea level rise in the Thames Estuary will reach between 0.26 and 0.86m by the year 2080, compared to its average level between 1961 and 1990 [15].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, equity is a measurement tool for social sensitivity to climate change and pays needed attention to populations most vulnerable to climate change impacts [31]. Some studies also highlight the necessity of developing communication mechanisms among heritage institutions, academic researchers, and the local community to build adaptation capacity at heritage sites [13,32]. Communication is essential for adapting to climate change because it facilitates the engagement of the public in climate change science and solutions in partnership with governments, media organizations, companies, and civil society [33].…”
Section: Introductionmentioning
confidence: 99%